2016
DOI: 10.1016/j.jecp.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Vocal overimitation in preschool-age children

Abstract: Overimitation--copying incorrect, idiosyncratic, or causally irrelevant actions--has been linked to our species' long history with artifacts whose functions are often opaque. It is an open question, however, whether children overimitate outside the artifact domain. We explored this question by presenting preschool-age children (3- to 5-year-olds, N=120) with an elicited imitation task that included high- and low-frequency disyllabic nouns (e.g., 'pizza) and nonwords (e.g., 'chizza), all of which had a stressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Over-imitation: a review and appraisal measure the same phenomenon, such as studies which operationalized OI via alternative options to act, one of which is less efficient than the other. However, we believe that clarity is gained by specifying some core boundaries in what qualifies as an instance of OI; for example, that OI should be restricted to the action domain and not be extended to the vocal domain (Subiaul, Winters, Krumpak, & Core, 2016). Word learning and communication are so intrinsically conventional that any "transparency" of what might constitute an irrelevant aspect to copy must be intrinsically fuzzy or nonexistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over-imitation: a review and appraisal measure the same phenomenon, such as studies which operationalized OI via alternative options to act, one of which is less efficient than the other. However, we believe that clarity is gained by specifying some core boundaries in what qualifies as an instance of OI; for example, that OI should be restricted to the action domain and not be extended to the vocal domain (Subiaul, Winters, Krumpak, & Core, 2016). Word learning and communication are so intrinsically conventional that any "transparency" of what might constitute an irrelevant aspect to copy must be intrinsically fuzzy or nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…A relatively new development is the expansion of the OI concept to the vocal or linguistic domain Subiaul, Winters, Krumpak, & Core, 2016). For example, Subiaul et al (2016) found that preschoolers adopted a model's unusual pronunciation in a word naming task and defined this vocal imitation as an instance of OI outside the artifact domain. As such findings do not meet our criteria for OI we will not discuss them further.…”
Section: Action Goalmentioning
confidence: 99%
“…DFSABC combines the educational value brought by the vocal music course with the vocal music practice. After investigation and analysis, it puts forward the strategy of implementing the core quality of students' development in the basic education stage [ 15 ]. Joer et al studied the connection between the core accomplishment and the singing teaching part of the junior high school vocal music course and considered that the “three-dimensional goals” of emotion, attitude, values, process and method, knowledge, and skills are the basis of the core accomplishment [ 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…In fact, young children's heightened sensitivity to subtle pronunciation differences may be one reason why they have such difficulty at first in understanding novel accents (e.g., Nathan, Wells, & Donlan, 1998). Children may also be more motivated to imitate novel pronunciations than adults are (Subiaul, Winters, Krumpak, & Core, 2016).…”
Section: The Effect Of Language Variation On Social Inferences and mentioning
confidence: 99%